(untitled) (LEARNing Landscapes, 2018)
Story is experience held in memory and story is the spark for a transformative possibility in the moment of its telling. The words we use are equally significant. This commentary reflects upon why words, stories, and oracy are powerful in learning landscapes. Indigenous peoples have known the value of story and the significance of words in creating and sustaining relationships. In an era of Truth and Reconciliation as Canadian postsecondary institutions seek to indigenize, the words we use and the stories we share will matter.